Pengaruh Perbedaan Pemberian Jenis Makroalga Sebagai Pakan Alami Pada Budidaya Abalon Haliotis Squamata - Iskandar, Andri; Naily, Alifah; Harsono, Agus; Hendriana, Andri (Jurnal TILAPIA, 2025)
The abalone Haliotis squamata is a fishery commodity with significant development potential. The efforts to increase abalone production can be achieved through aquaculture. In Indonesia, most abalone production still comes from wild catches. One of the key factors in successful abalone farming is the quality of the feed provided. Therefore, studies on abalone feed are necessary to improve growth, survival, and overall farming productivity. Such research is also essential to support sustainable production without dependence on wild catches. The purpose of this study is to assess abalone growth and survival in relation to the availability of various macroalgae diets, enabling the identification of the optimal macroalgae type to promote abalone growth and survival. In this study, Gracilaria sp. and Ulva reticulata were used as abalone feed. Analysis of variance (ANOVA) was used to examine the data. According to the study, the growth patterns created by the two feed types were comparatively similar. Both types of macroalgae were consumed by abalone with a normal response, causing no toxicity or stress, making them suitable options as primary abalone feed.